2018
DOI: 10.1039/c8fo01161c
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid directly targets pyruvate kinase isoenzyme M2 to attenuate colon cancer cell proliferation

Abstract: Tannic acid (TA), a naturally occurring polyphenolic acid that is primarily found in grapes and green tea, exhibits potent antioxidant and anticarcinogenic characteristics. However, the underlying molecular mechanisms and targets of TA, which are responsible for cancer prevention, remain elusive. In the present study, we used TA-functionalized magnetite nanoparticles to identify pyruvate kinase isoenzyme M2 (PKM2) as the direct target of TA. We report that TA selectively inhibits the pyruvate kinase activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…In our study, we found that PB2 enhanced the effect of SORA on HCC both in vivo and in vitro by targeting PKM2. Emerging evidence has revealed that botanic flavonoids, including oroxylin A, tannic acid, and genistein, enhance the chemosensitivity to SORA [11, 48, 49]. Because PB2 is a nontoxic agent to L02 cells and mice, PB2 is a promising agent to act as a chemopreventive or chemotherapeutic medicine to treat HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that PB2 enhanced the effect of SORA on HCC both in vivo and in vitro by targeting PKM2. Emerging evidence has revealed that botanic flavonoids, including oroxylin A, tannic acid, and genistein, enhance the chemosensitivity to SORA [11, 48, 49]. Because PB2 is a nontoxic agent to L02 cells and mice, PB2 is a promising agent to act as a chemopreventive or chemotherapeutic medicine to treat HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This finally induces cell cycle arrest as described for HCT116 cells 38 , supported by our own observations. TA is thus considered a potential anticancer agent [39][40][41] , with additional ability to act as chemosensitizer 42 . The latter is a characteristic quite common for other polyphenols as well.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the therapeutic effect of TA, a recent study even proposed this substance as a promising pyruvate kinase isoenzyme M2 inhibitor for CRC prevention 39 . Still, clinical evidence of dietary polyphenols as chemopreventive compounds is scarce and at least partially attributable to the fact that TA concentrations in the gastrointestinal tract are hardly measurable and backtracked to mediate a direct tumor growth inhibitory effect.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methods of cell culture were described in our previous studies 31 . Cell proliferation was detected by MTT assay and EdU assay 32 . A clonogenic assay was carried out as previously reported 32 .…”
Section: Methodsmentioning
confidence: 99%